Holistic nursing care among operating room nurses: Strengthening the standard of practice in Saudi Arabia - Hamdan Mohammad Albaqawi; Vincent Edward Butcon; Bander Saad Albagawi; Richard Dennis Dayrit; Petelyne Pangket (Belitung Nursing Journal, 2021)
Background: Holistic practices have been found beneficial for patients as well as nurses. They increase both the nurses and the patients’ health-promoting behaviors, spirituality, and interpersonal relationships. Objective: This study aimed to determine holistic nursing care and compare its differences based on individual characteristics. Methods: This study employed a quantitative-cross sectional approach. It was conducted at the hospitals of Hail region, Kingdom of Saudi Arabia, from February 2020 to March 2020. Selected through convenience sampling, 154 operating room nurses participated in the study. Frequency and percentages were used to analyze the demographic information, and t-tests and analysis of variance were used to test for differences. Results: Holistic nursing dimensions such as physiological (4.72 ± 0.40), socio-cultural (4.53 ± 0.45), psychological (4.66 ± 0.32), and spiritual aspects (4.22 ± 0.73) were consistently carried out in the operating room. On the physiological dimension, no significant differences were found in years of experience [(t) -0.073; p > 0.942], gender [(t) -1.113; p > 0.27], or age [(F) 0.558; p > 0.57), but there was a significant difference with nationality [(t) -3.328; p < 0.001]. On the socio-cultural dimension, the length of experience [(t) 0.599; p > 0.550], gender, [(t) -1.420; p > 0.158], and age [(F) 0.148; p > 0.862] were not significant, but a significant difference was found with nationality [(t) -7.516; p < 0.001]. Regarding the psychological dimension, the length of experience [(t) -1.101; p > 0.276], gender [(t) -1.545; p > 0.129], and age [(F) 1.259; p > 0.287] were not significant, but there was a significant difference with nationality [(t) -5.492; p < 0.001]. Finally, with the spiritual dimension, no significant difference was found on length of experience [(t) -1.101; p > 0.276] or age [(F) 0.584; p > 0.559], but there were significant differences on gender [(t) -3.890; p < 0.001] and nationality [(t) -3.653; p < 0.001]. Conclusion: Nationality is a causal factor to physiological, socio-cultural, psychological, and spiritual dimensions, while gender is significant to spiritual aspect. Regardless of nationality or gender, nurses must be knowledgeable regarding the significance of adopting holistic care to improve the quality of their care to their patients.